Strengthening Mathematical Competencies in Fourth Grade Students through a Gamified Digital Literacy Didactic Model (Docentes 2.0 Journal, 2024)
The accelerated advancement in the scientific and technological field, particularly in Information and Communication Technologies (ICT), demands an educational approach that encourages creativity and innovative thinking among students. The study's main objective was to propose an innovative educational model integrating gamification, digital literacy, and technology to improve mathematics teaching. The research was based on the holographic method, a holistic paradigm with a mixed approach, descriptive, propositional-transrectal, and projective design. The target population included 108 fourth-grade students in Bogotá, Colombia, and questionnaires, mathematical competency tests, and digital skills assessments were used as data collection instruments. These were structurally validated, and their reliability was determined using Cronbach's alpha. A Spearman correlation analysis using SPSS software revealed a positive, significant correlation between digital literacy and students' mathematical competencies, indicating a close association between these aspects. The findings reflected a low level of mathematical competencies attributed to cognitive and methodological deficiencies in the students. In summary, the proposed teaching model represents a technological tool that improves teaching and learning dynamics by integrating technology, gamification, and mathematics teaching to increase the interest and participation of students in this discipline.
Keywords: Digital literacy; mathematical skills; gamified; didactic model